Examining the safety of mirabegron: an analysis of real-world pharmacovigilance data from the US FDA adverse event reporting system (FAERS) database - Wang, Junwei; Zhang, Aiwei; Ye, Miaoyong; Zhang, Cunming (Frontiers in Pharmacology, 2024)
Background: Mirabegron, the first β-3 adrenergic receptor agonist, received approval from the Food and Drug Administration (FDA) in 2012 for the treatment of overactive bladder (OAB). This pharmacovigilance study investigated the safety profile of mirabegron treatment using the US FDA Adverse Event Reporting System (FAERS) database. Methods: This study employed disproportionality analyses, including the reporting odds ratio (ROR) and Bayesian Confidence Propagation Neural Network (BCPNN) algorithm, to quantify signals of adverse events associated with mirabegron. Results: From the first quarter of 2012 to the third quarter of 2023, a comprehensive total of 14,356,234 adverse event (AE) reports were submitted to the FDA Adverse Event Reporting System database. Within this dataset, encompassing 18,763 reports specifically associated with mirabegron, healthcare professionals notably contributed 2,902 of these reports. A total of 80 preferred terms (PTs) of interest were identified using both the ROR and information component algorithms. The most common AEs included blood pressure increased, urinary retention, atrial fibrillation, dry mouth, and tachycardia, which were consistent with the product instructions. Unexpected significant AEs, such as arrhythmia, palpitations, dementia, transient ischemic attack, Parkinson’s disease, anti-neutrophil cytoplasmic antibody positive vasculitis, lip swelling, and swollen tongue, were also identified. The study findings indicated that the majority of onset time occurred within 30 days (n = 358, 55.68%). However, AEs were still possible after 1 year of mirabegron treatment. Conclusion: This study provided valuable evidence for the real-world safety of mirabegron, helping clinical professionals enhance their understanding of mirabegron’s safety in clinical practice. It also contributed valuable evidence for further safety studies on mirabegron.